TINDAKAN ULTRA VIRES PENGURUSAN OPERASIONAL PERSEROAN TERBATAS OLEH KOMISARIS - Sekar, Raden Roro Ayu; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
One of the organs of a Limited Liability Company (PT) is the commissioner whose main task is to provide the Directors with advice and general supervision in running a Limited Liability Company (PT). A Limited Liability Company (PT) is established based on an agreement in the form of a legal entity and carries out a capital partnership, carries out business activities with authorized capital which is entirely divided into shares and meets the requirements stipulated in this law and its implementing regulations. In carrying out the duties and authority that have been regulated in the articles of association of a Limited Company (PT), actions may occur that exceed the limits of authority or can be called ultra vires. This research was conducted with the aim of finding out whether the Commissioner's actions in managing the operations of a Limited Company (PT) were Ultra Vires actions. By using normative juridical research methods from Law Number 40 of 2007 concerning Limited Liability Companies and examining library materials or secondary data. The results of this research are that the duties and authority of the commissioner are not to carry out operational management, but in certain circumstances operational management can be carried out, provided that there is a valid reason for carrying out the action. If there is no valid reason then the action is ultra vires.Keywords: Commissioner, Limited Liability Company, Ultra Vires